Perkembangan Tarekat Naqsyabandiyah di Bonjol Sumatera Barat Abad ke-19 M - Sabrina, Sabrina; Zuhairi, Muhammad; Rahayu, Nike; Hidayat, Rahmat (Warisan: Journal of History and Cultural Heritage, 2022)
This article aims to review Bonjol's existence as one of the teaching centers of the Naqsyabandiyah Order which were founded by Syekh Maulana Ibrahim Al-Khalidi, the most influential Naqsyabandiyah sheikh in the Minangkabau area in the 19th century. His teaching at Bonjol made many scholars come to Bonjol to study with him so which gave birth to a network of new scholars in West Sumatra and North Sumatra. This research is a literature study using historical methods. Several manuscripts were used as primary sources and several books and relevant scientific articles were used as secondary sources. The conclusion of this study is that Bonjol is an important place for the development, dissemination, and main support for the popularity of the Naqsyabandiyah Order in West Sumatra in the 19th century AD.